Assessment of the European classification criteria for Sjögren's syndrome in a series of clinically defined cases: results of a prospective multicentre study. The European Study Group on Diagnostic Criteria for Sjögren's Syndrome. Issue 2 (February 1996) - Vitali, C; Bombardieri, S; Moutsopoulos, H M; Coll, J; Gerli, R; Hatron, P Y; Kater, L; Konttinen, Y T; Manthorpe, R; Meyer, O; Mosca, M; Ostuni, P; et al.
Abstract : OBJECTIVE: To assess the recently proposed preliminary criteria for the classification of Sjögren's syndrome (SS) in a multicentre European study of a new series of clinically defined cases. METHODS: The criteria included six items: I = ocular symptoms; II = oral symptoms; III = evidence of keratoconjunctivitis sicca; IV = focal sialoadenitis by minor salivary gland biopsy; V = instrumental evidence of salivary gland involvement; VI = presence of autoantibodies. Each centre was asked to provide five patients with primary SS, five with secondary SS, five with connective tissue diseases (CTD) but without SS, and five controls (patients with ocular or oral features that may simulate SS). The preliminary six item classification criteria set was applied to both the SS patients and the non-SS controls, and the performance of the criteria in terms of sensitivity and specificity was tested. RESULTS: The criteria set was tested on a total of 278 cases (157 SS patients and 121 non-SS controls) collected from 16 centres in 10 countries. At least four of the six items in the criteria set (limiting item VI to the presence of Ro(SS-A) or La(SS-B) antibodies) were present in 79 of 81 patients initially classified as having primary SS (sensitivity 97.5%), but in only seven of 121 non-SS controls (specificity 94.2%). When the presence of item I or II plus any two of items III-V of the criteria set was considered as indicative of secondary SS, 97.3% (71 of 73) of the patients initially defined as having this disorder and 91.8% (45 of 49) of the control patients with CTD without SS were correctly classified. CONCLUSION: This prospective study confirmed the high validity and reliability of the classification criteria for SS recently proposed by the European Community Study Group.